Factors Affecting Employee Performance at the Communication Information and Statistics Department Bengkulu Province - Wike Safitri; Suwarni Suwarni; Tito Irwanto (Penerbit Jurnal Indonesia, 2022)
The purpose of this study is to determine the factors affecting employees performance at at the Department of Information Communication and Statistics Bengkulu Province. These factors refer to Sanjaya's opinion which consists of employee internal factors, organizational internal environmental factors and organizational external environmental factors. This research is descriptive research using the overall sampling method (saturated sampling) with a total population of 87 employees of the State Civil Apparatus. The data collection method in this study used a questionnaire method with the distribution of questionnaires in the form of a list of statements in the form of a Likert scale. The method of analysis in this research is multiple linear regression analysis. The results of this study indicate that the variable internal employee factors affect employee performance by 3.561 with a significance level of 0.001. Variable internal organizational environmental factors also affect employee performance of 5.413 with a significance level of 0.000. While the organizational external environmental factor variable of 0.999 has no effect on employee performance because the level of significance is greater than 0.05 or 0.321. Simultaneously, employee internal factors, organizational internal environmental factors and organizational external environmental factors have a significant effect on employee performance of 30.663 with a significance level of 0.000, so the hypothesis can be accepted.